Glucose metabolism and endometrium decidualization - Huang, Yunfei; Zhu, Qinling; Sun, Yun (Frontiers in Endocrinology, 2025)
Prior to embryo implantation, the endometrial stromal cells (ESCs) during the menstrual cycle undergo a significant structural and functional transformation known as decidualization to support conception. During this process, glucose consumption and utilization by endometrial cells increase to meet energy demands. Abnormal glucose metabolism in the endometrium impairs decidualization, leading to pregnancy complications, including implantation failure and pregnancy loss. However, the mechanisms modulating glucose metabolism in endometrial stromal cells during decidualization are still unclear. In this review, we describe the functions and regulation of glucose transporters (GLUTs) involved in glucose uptake, as well as the modulation of key enzymes catalyzing glucose utilization. Moreover, we present recent findings on the role of glucose related metabolites in the decidualization of ESCs.